Establishment Of A Novel RT- Qpcr Assay For The Detection Of Mutations In Myeloproliferative Neoplasms (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Myeloproliferative Neoplasms (MPNs) are rare heterogeneous hematological disorders usually characterized by one or more lineages of myeloid cells in bone marrow and increase number of normal and abnormal cells. Janus kinase 2 valine to phenylalanine (JAK2-V617F) is usually present in Philadelphia-negative MPNs. Pathogenic mutation in JAK2-V617F cause’s valine to phenylalanine substitution in JAK2 gene on exon-14. Different techniques such as Amplification refractory mutation system (ARMS-PCR), Allele-specific PCR (AS-PCR), High resolution melting (HRM) analysis and Molecular beacon probe-based RT-PCR are already available to diagnose JAK2-V617F mutation.Method: Current study aimed to develop and optimize real-time PCR assay which will be available locally and be feasible, less expensive and less labor extensive. The DNA was extracted from 128 patients and analyzed on our optimized method using newly designed primers and probe. Standards were generated using in-vitro synthesized sequence (Kinco Biological) and Standard curve was obtained.Result: Predicted sensitivity of the method is at least5% for allele burden of the mutation. The total of 128 MPN patients were included in the present study and 54 (42.1%) were JAK2-V617Fpositive according to the optimized protocols.Conclusion: The study concluded that TaqMan Real time qPCR is efficient, sensitive and less expensive for the detection of JAK2-V617F mutation.